Meta-Analysis Comparing WatchmanTM and Amplatzer Devices for Stroke Prevention in Atrial Fibrillation - Basu Ray, Indranill; Khanra, Dibbendhu; Shah, Sumit; Char, Sudhanva; Jia, Xiaoming; Lam, Wilson; Mathuria, Nilesh; Razavi, Mehdi; Jain, Bhavna; Lakkireddy, Dhanunjaya; Kar, Saibal; Natale, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2020)
BACKGROUND: For patients with atrial fibrillation who are at high risk for bleeding or who cannot tolerate oral anticoagulation, left atrial appendage (LAA) closure represents an alternative therapy for reducing risk for thromboembolic events. OBJECTIVES: To compare the efficacy and safety of the Amplatzer and Watchman LAA closure devices. METHODS: A meta-analysis was performed of studies comparing the safety and efficacy outcomes of the two devices. The Newcastle-Ottawa Scale was used to appraise study quality. RESULTS: Six studies encompassing 614 patients were included in the meta-analysis. Overall event rates were low for both devices. No significant differences between the devices were found in safety outcomes (i.e., pericardial effusion, cardiac tamponade, device embolization, air embolism, and vascular complications) or in the rates of all-cause mortality, cardiac death, stroke/transient ischemic attack, or device-related thrombosis. The total bleeding rate was significantly lower in the Watchman group (Log OR= -0.90; 95% CI= -1.76 to -0.04; p=0.04), yet no significant differences was found when the bleeding rate was categorized into major and minor bleeding. Total peridevice leakage rate and insignificant peridevice leakage rate was significantly higher in the Watchman group (Log OR= 1.32; 95% CI= 0.76 to 1.87; p<0.01 and Log OR= 1.11; 95% CI= 0.50 to 1.72; p<0.01 respectively). However, significant peridevice leakages were similar in both the devices. CONCLUSIONS: The LAA closure devices had low complication rates and low event rates. Efficacy and safety were similar between the systems, except for a higher percentage of insignificant peridevice leakages in the Watchman group. A randomized controlled trial comparing both devices is underway which may provide more insight on the safety and efficacy outcomes comparison of the devices.